Cause-consequence analysis of conversion of paddy fields in Kuttanad - Mercykutty M J (Department of Agricultural Extension, College of Horticulture, 2002)
The keynote of Kerala's agriculture is the diversity in crop production, which is the consequence of a wide range of natural conditions. The food habits and the consumption pattern have made rice the staple food of the people of Kerala. A major land use change that has occurred in Kerala is the conversion and reclamation of paddy cultivated areas, both in the low lands and uplands to agricultural and non- agricultural purposes jeopardizing the food security of the state, when it is designated as a "Statutory Ration State" with over sixty percent need of food grains met by imports. Several pnmary observations in different locations of the state where extensive wetland conversion has taken place indicated significant consequences. It is estimated that more than forty percent of the population in the Kuttanad region is engaged in rice cultivation. In this background the study was designed to fmd out the nature and extent of conversion of paddy fields in Kuttanad. It was also aimed to analyse the push-pull factors influencing the conversion and socio-economic consequences of conversion of paddy fields. The agro ecosystem impact as perceived by the respondents was also analysed. The study was also aimed to develop a suitable strategy to rationalise the land use pattern to check the conversion process. The study was conducted in three panchayats viz. Thakazhi and Thalavady from Alappuzha District and Vazhappally from Kottayam District. The different types of respondents included convertor and non-convertor farmers, agricultural labourers, agricultural scientists, extension workers, people's representatives and social activists. Data were collected through personal interview using well structured interview schedule, group discussion, focus group interviews, key informant interviews, oral history innovations, personal field level observations and local inquiry methods. Different parametric and non-parametric statisti~al\ tools were used for analyzing the data.